Strategic Role of Islamic Religious Education in Character Building in the Digital Era: A Theoretical and Practical Analysis - Septianingsih, Wulan; Amalia, Rizki; Oktafiani, Diana (PPSDP International Journal of Education, 2024)
This study examines the strategic role of Islamic Religious Education (PAI) in shaping students’ character, particularly in the rapidly advancing digital era. The aim of this study is to explore how PAI contributes to students’ development of essential moral values and ethical responsibilities in their use of technology. Utilizing a qualitative descriptive methodology through a literature review approach, this research provides an in-depth analysis of existing literature on the integration of religious values in education, particularly in the context of digital media. The results reveal that PAI acts as a “moral filter,” guiding students to critically assess information, distinguish reliable from misleading content, and interact wisely in digital environments. These values not only help students make ethical decisions but also equip them to be responsible and respectful digital citizens. However, a significant challenge identified is the limited technological proficiency among PAI educators, which can hinder the effectiveness of digital-based learning. This gap in digital competence impacts educators’ ability to integrate technology meaningfully into lessons, thus reducing the potential impact of PAI education. Therefore, the study highlights the importance of digital training for educators to enhance their capacity to deliver PAI content in ways that are engaging, interactive, and relevant for tech-savvy students. This study contributes to the educational field by demonstrating that PAI not only fosters academic excellence but also plays a pivotal role in building resilient, ethically grounded individuals who are equipped to navigate the complexities of the digital age responsibly.